Mapping of Mangrove Crab Breeding Locations in the Coastal District of Aceh Jaya - Nurul Hidayat; Asiah Asiah; Wardiah Wardiah; Djufri Djufri; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Mud crab is an aquatic species that generally lives in the mangrove ecosystem. Aceh Jaya Regency has a mangrove ecosystem as a habitat for various organisms, especially mangrove crabs that need protection from damage and pollution. This study aims to determine the area of mangrove crab breeding sites in Aceh Jaya Regency. This study used observation and interview methods with a qualitative descriptive approach. The data obtained is described descriptively and presented in the form of maps and tables. The results of the study are that mud crab breeding sites are easy to find, with ecosystem environmental quality that supports the growth and breeding of mud crabs which is characterized by the diversity of mangrove species and aquatic species as a supporting factor for mud crab breeding sites.Keywords: mud crab, mangrove ecosystem, breeding siteKepiting bakau merupakan spesies perairan yang umumnya berhabitat dikawasan ekosistem mangrove. Kabupetan Aceh Jaya memiliki ekosistem mangrove sebagai habitat berbagai organisme terutama kepiting bakau yang memerlukan perlindungan dari kerusakkan dan pencemaran. Penelitian ini bertujuan untuk mengetahui kawasan breeding site kepting bakau di Kabupaten Aceh Jaya. Penelitian ini menggunakan metode observasi dan wawancara dengan pendekatan deskriptif kualitatif. Data yang diperoleh diuraikan secara deskriptif dan disajikan dalam bentuk peta dan tabel. Hasil penelitian yaitu kawasan breeding site kepiting bakau mudah ditemukan, dengan kualitas lingkungan ekosistem yang mendukung pertumbuhan dan perkembangbiakan kepiting bakau yang ditandai dengan keberagaman spesies mangrove dan spesies perairan sebagai faktor pendukung breeding site kepiting bakau.Kata kunci: kepiting bakau, ekositem mangrove, breeding site